ILRI research on livestock, food safety and human health - Grace, Delia (International Livestock Research Institute, 2011)
For the November 2011 'liveSTOCK Exchange' event at the International Livestock Research Institute (ILRI), Delia Grace, reflects on ILRI's research in agriculture for human health and nutrition.